2021
DOI: 10.1002/pros.24191
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world evidence with The Rezūm System: A retrospective study and comparative analysis on the efficacy and safety of 12 month outcomes across a broad range of prostate volumes

Abstract: Background To provide 12‐month unbiased outcomes with The Rezūm System (Rezūm), a convective water vapor thermal therapy for patients with lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia (BPH). Results from this retrospective, real‐world evidence (RWE) study were compared to those of previous studies with the aim to evaluate the device's safety and efficacy in a real‐world patient population. Methods Patients 45 years or older with an International Prostate Symptom Score (IPSS) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Significant percent improvements from baseline to 3 months in IPSS, QoL, and Qmax ranged between 36% and 80% (median 51%), 32% to 86% (median 51%), and 32% to 130% (median 66%), respectively. Out of the seven studies 11‐19,21,25,26,33 that evaluated PVR from baseline to 3, 6 to 7.2, and 12 months, only two studies 21,26 found it to be significantly improved at all three follow‐ups (median percent improvements 54%, 56%, and 57%, respectively) (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Significant percent improvements from baseline to 3 months in IPSS, QoL, and Qmax ranged between 36% and 80% (median 51%), 32% to 86% (median 51%), and 32% to 130% (median 66%), respectively. Out of the seven studies 11‐19,21,25,26,33 that evaluated PVR from baseline to 3, 6 to 7.2, and 12 months, only two studies 21,26 found it to be significantly improved at all three follow‐ups (median percent improvements 54%, 56%, and 57%, respectively) (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…However, only the results from the cohort who underwent Rezum were included in this review. Bole et al 28 Garden et al, 29 and Ines et al 33 included subanalyses of patients with large baseline prostate volumes in which 26%, 18%, and 7% of patients, respectively, had baseline prostate volumes of >80 g. Additionally, Ines et al 33 also included a subanalysis of patients with small baseline prostate volumes (<30 g). McVary et al 27 Baboudjian et al 34 Bassily et al 35 Besides the pilot study by Dixon et al 18,19 all the studies were conducted in the United States before 2020.…”
Section: Study Patient and Procedural Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations